MTOR Inhibition by Everolimus Does Not Impair Closure of Punch Biopsy Wounds in Renal Transplant Patients. Issue 4 (April 2017) - Dutt, Shelley B.; Gonzales, Josephine; Boyett, Megan; Costanzo, Anne; Han, Peggy P.; Steinberg, Steven; McKay, Dianne B.; Jameson, Julie M.
Abstract : Background: Mammalian target of rapamycin (mTOR) inhibitors are approved to prevent allograft rejection and control malignancy. Unfortunately, they are associated with adverse effects, such as wound healing complications that detract from more extensive use. There is a lack of prospective wound healing studies to monitor patients treated with mTOR inhibitors, such as everolimus or sirolimus, especially in nondiabetics. Methods: Patients receiving everolimus with standard immunosuppressant therapy or standard immunosuppressant therapy without everolimus were administered 3-mm skin biopsy punch wounds in the left scapular region. Homeostatic gene expression was examined in the skin obtained from the biopsy and wound surface area was examined on day 7. Peripheral blood mononuclear cells were examined for cytokine production. Results: There are no significant changes in autophagy related 13, epidermal growth factor, insulin-like growth factor binding protein 3, IL-2, kruppel-like factor 4, and TGFB1 gene expression in the skin suggesting that there is little impact of everolimus on these genes within nonwounded skin. Peripheral blood T cells are more sensitive to cell death in everolimus-treated patients, but they retain the ability to produce proinflammatory cytokines required for efficient wound repair. Importantly, there is no delay in the closure of biopsy wounds in patients receiving everolimus as compared to those not receiving mTOR inhibition. Conclusions: Everolimus treatment is not associated with impaired closure of skin biopsy wounds in kidney transplant recipients. These data highlight the importance of exploring whether larger surgical wounds would show a similar result and how other factors, such as diabetes, impact wound healing complications associated with mTOR suppression.